2009
DOI: 10.1080/10826060903392939
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Activity of Bubbling-Immobilized Cellobiase Within Chitosan-Alginate Composite

Abstract: Cellobiase can hydrolyze cellobiose into glucose; it plays a key role in the process of cellulose hydrolysis by reducing the product inhibition. To reuse the enzyme and improve the economic value of cellulosic ethanol, cellobiase was immobilized using sodium alginate and chitosan as carriers by the bubbling method. The immobilization conditions were optimized as follows: enzyme loading of 100 U cellobiase/g carrier, 30 min immobilization, 3.5 wt% sodium alginate, 0.25 wt% chitosan, and 2 wt% calcium chloride. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…To decrease reducing product inhibition effect on cellobiohydrolase and β-glucosidase, simultaneous saccharification and fermentation is often used in bioethanol production by fermentable sugars to ethanol timely [7][8][9]. At the same time, other strategies were performed for the purpose of cost-effective enzymatic conversion, such as reducing enzymes production cost, producing cellulase with higher specific activity [10], enzyme recycling including cellulase adsorption onto fresh substrate [11], and cellulase immobilization [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…To decrease reducing product inhibition effect on cellobiohydrolase and β-glucosidase, simultaneous saccharification and fermentation is often used in bioethanol production by fermentable sugars to ethanol timely [7][8][9]. At the same time, other strategies were performed for the purpose of cost-effective enzymatic conversion, such as reducing enzymes production cost, producing cellulase with higher specific activity [10], enzyme recycling including cellulase adsorption onto fresh substrate [11], and cellulase immobilization [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Use of a 50:50 blend ratio of Cs to PCL, processed at 55 • C in an oven, produced composites that showed significant improvement in mechanical properties with tensile strength up to 4.5 MPa and strain 25%, respectively [246,247]. In addition, measured cellular activity results suggested that the chloroform as solvent for blending process did not produce any cytotoxicity in the blend [248,249]. The miscibility of the blend was proven by a shift in adsorption peak from 1743.9 to 1724.8 cm −1 due to the C=O groups of PCL, which indicated an interaction between the blending components [242,250,251].…”
Section: Cs/poly-ε-caprolactone Blendmentioning
confidence: 89%
“…Among the multi-enzyme complex for cellulosic hydrolysis, β-glucosidase is frequently used to supplement cellulase preparations for hydrolysis of cellobiose to glucose. In recent years, some inert materials, such as chitosan-alginate composite [111], chitosan-clay composite [112], Eupergit C [113], mesoporous silicates [114], silica gel and Kaolin [115], had been identified as Fig. 3 The strategies of enzymes recycling and their main characteristics efficient carriers for immobilization of commercial β-glucosidase via physical adsorption or covalent binding.…”
Section: Enzyme Recycling and Reusementioning
confidence: 99%